2014
DOI: 10.1371/journal.pone.0102178
|View full text |Cite
|
Sign up to set email alerts
|

A Subset of Circulating Blood Mycobacteria-Specific CD4 T Cells Can Predict the Time to Mycobacterium tuberculosis Sputum Culture Conversion

Abstract: We investigated 18 HIV-negative patients with MDR-TB for M. tuberculosis (Mtb)- and PPD-specific CD4 T cell responses and followed them over 6 months of drug therapy. Twelve of these patients were sputum culture (SC) positive and six patients were SC negative upon enrollment. Our aim was to identify a subset of mycobacteria-specific CD4 T cells that would predict time to culture conversion. The total frequency of mycobacteria-specific CD4 T cells at baseline could not distinguish patients showing positive or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…The presence of CD4 + IFN-γ + T cells in PBMCs from both ATB and LTBI groups was assessed by flow cytometry and intracellular to more rapidly identify delayed responsiveness or nonresponsiveness to anti-TB treatment (e.g., in patients infected with drug-resistant strains) compared with sputum culture and may predict sputum conversion. In this regard, it has recently been suggested that the coexpression of HLA-DR + Ki-67 + on Mtb and purified protein derivative-specific (PPD-specific) CD4 + T cells predicts the time of sputum culture conversion in patients with MDR-TB (48). Notably, CD38…”
Section: Methodsmentioning
confidence: 99%
“…The presence of CD4 + IFN-γ + T cells in PBMCs from both ATB and LTBI groups was assessed by flow cytometry and intracellular to more rapidly identify delayed responsiveness or nonresponsiveness to anti-TB treatment (e.g., in patients infected with drug-resistant strains) compared with sputum culture and may predict sputum conversion. In this regard, it has recently been suggested that the coexpression of HLA-DR + Ki-67 + on Mtb and purified protein derivative-specific (PPD-specific) CD4 + T cells predicts the time of sputum culture conversion in patients with MDR-TB (48). Notably, CD38…”
Section: Methodsmentioning
confidence: 99%
“…Animals vaccinated with MtbΔ sigH displayed higher frequencies of Mtb cell wall- and culture filtrate protein-responsive polyfunctional CD4 + T cells compared with unvaccinated animals. Recent data have shown that markers of T-cell immune activation in human TB are associated with smear and culture conversion during anti-TB treatment 58 . Nonetheless, the current study had some limitations; for example, protection was only demonstrated in a homologous strain.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, persons with latent infection exhibit higher frequencies of trifunctional IFN‐γ + TNF + IL‐2 + M. tuberculosis ‐specific CD4 + T cells . Furthermore, TB treatment appears to drive the CD4 + T‐cell compartment to a more trifunctional IFN‐γ + TNF + IL‐2 + state . Other studies, however, have found that active TB disease is accompanied by an expansion in the frequency of TNF + IFN‐γ + IL‐2 + CD4 + T cells, as compared to latent infection or to after TB treatment .…”
Section: T‐cell Activation After M Tuberculosis Infectionmentioning
confidence: 91%